FILSAFAT HUKUM PANCASILA: ANTARA CITA IDEAL HUKUM DAN NILAI PRAKSIS - Fokky Fuad (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
Pancasila in giving meaning often changes according to time and space. For those reasons, the Pancasila as part of the School of Philosophy of Law is not to be in a vacuum. He unearthed by our Founding Fathers thought that looking for the basic values ​​for the creation of the State of Indonesia from sediment values ​​of the nation. The magical religious values ​​and solidarity expressed by the Bung Karno as mutual assistance has undergone a shift in meaning according to time and space. The Clash that has occurred creating adaptive values ​​as a form of dialogue processes between the value.